Morphological and ecological variation of a tropical anoline lizard: are agonistic interactions shaping ecomorphological relationships? - Barquero Arroyo, Marco David (2018)
Ecologists have long been intrigued by which factors influence habitat use by an organism and how communities are structured. However, the links between habitat preferences, morphology, biotic interactions and community structure are still poorly understood. Moreover, interpopulation variation in ecomorphological relationships has usually been neglected. Here, we use a wide-ranging Anolis lizard, Anolis limifrons, to test whether interpopulation variation in morphology and habitat use is a function of interspecific agonistic interactions across the distribution of this species in Costa Rica. We found differences both in morphology and in habitat use among populations of A. limifrons, with populations from the Caribbean versant of Costa Rica having longer hind legs and perching lower than those from the Pacific versant. The intensity of interspecific agonistic interactions also varied across versants, with A. limifrons from Pacific sites displaying more often to congeners than those from the Caribbean. Agonistic interactions appear to be an important factor shaping habitat use and morphology. These findings can be explained by an interaction between phenotypic plasticity and ecological plasticity.